Bank income smoothing, ownership concentration and the regulatory environment - Bouvatier, Vincent; Lepetit, Laetitia; Strobel, Frank (Journal of Banking & Finance, 2014)
We empirically examine whether the way a bank might use loan loss provisions to smooth its income is influenced by its ownership concentration and the regulatory environment. Using a panel of European commercial banks, we find evidence that banks with more concentrated ownership use discretionary loan loss provisions to smooth their income. This behavior is less pronounced in countries with stronger supervisory regimes or higher external audit quality. Banks with low levels of ownership concentration do not display such discretionary income smoothing behavior. This suggests the need to improve existing or implement new corporate governance mechanisms.